Understanding socio‐cultural influences on food intake in relation to overweight and obesity in a rural indigenous community of Fiji Islands. (21st August 2020) - Singh, Kamal Nand; Sendall, Marguerite C.; Gurung, Apil; Carne, Phil
Abstract: Issue addressed: Obesity and non‐communicable diseases (NCDs) are largely preventable by understanding the connection between socio‐cultural knowledge, yet intervention effectiveness may hinder changes in lifestyles and behaviours in Indigenous health. This study performed to understand the social and cultural components, which contribute to obesity in rural areas of the Indigenous Fijian. Methods: This study is a Community‐Based Participatory Research (CBPR) project, which engaged community members from a rural iTaukei village in the Fiji Islands. Data collection was carried out through community consultation and semi‐structured interviews. The data were analysed using descriptive thematic analysis. Results: Food intake was associated with socio‐cultural, economic, political and physical environmental factors. Participants reveal previous health promotion programs did not incorporate the cultural values, cultural competence beliefs and traditional ways of rural Indigenous Fijian community. Conclusion: The health care providers and policymakers need to be involved in recognising iTaukei community culture and appreciate traditional methods to promote equitable community participation in decision‐making for health promotion. So what?: Community‐wide lifestyle interventions, conceptual approaches based on communal perceptions of the problem at hand can also be the basis for future research on identifying socio‐cultural factors, for example, the community and family support that can help shape behaviours.